2011
DOI: 10.1002/hec.1623
|View full text |Cite
|
Sign up to set email alerts
|

Health plan enrollment and mortality in the Medicare program

Abstract: Prior studies have found that Medicare health maintenance organization (HMO) enrollees have lower mortality (over a fixed observation period) than beneficiaries in traditional fee-for-service (FFS) Medicare. We use Medicare Current Beneficiary Survey (MCBS) data to compare 2-year predicted mortality for Medicare enrollees in the HMO and FFS sectors using a sample selection model to control for observed beneficiaries characteristics and unobserved confounders. The difference in raw, unadjusted mortality probabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…21 Moreover, since 2003 both groups have experienced similar declines in overall mortality, lending support to the conclusion that the observed changes among the Fee-for-Service population are not the result of changes in the risks of the groups relative to each other and do represent true improvement. Moreover, other studies have found that healthier people are likely to shift enrollment from Fee-for-Service to Medicare Advantage, which may have led to an underestimation of the improvement over time, 22,23 because we observed increasing enrollment in Medicare Advantage over time.…”
Section: Discussionmentioning
confidence: 61%
“…21 Moreover, since 2003 both groups have experienced similar declines in overall mortality, lending support to the conclusion that the observed changes among the Fee-for-Service population are not the result of changes in the risks of the groups relative to each other and do represent true improvement. Moreover, other studies have found that healthier people are likely to shift enrollment from Fee-for-Service to Medicare Advantage, which may have led to an underestimation of the improvement over time, 22,23 because we observed increasing enrollment in Medicare Advantage over time.…”
Section: Discussionmentioning
confidence: 61%
“…However, the generosity of competitor plans should not directly influence the drug therapy utilization of the beneficiary, making it a valid instrument. Previous studies on health plan enrollment have used information from competitor plans as the instrumental variable to account for endogenous plan selection (Mello, Stearns, and Norton 2002;Dowd et al 2010). While a potential alternative instrument could be based on the market shares of competitor plans, the 5 percent sample cannot support such an approach.…”
Section: Statistical Modelsmentioning
confidence: 99%
“…This makes it difficult to determine whether managed care improves health or simply attracts the healthy. Those studies that used econometric approaches to correct for this bias have focused on a limited number of self-report and mortality outcomes (Mello et al, 2002; Rizzo, 2005; Balsa et al, 2007; Huesch, 2010; Dowd et al, 2011). This study uses administrative data covering the universe of hospitalizations in Arizona, Florida, New Jersey and New York from 1999 through 2005, states where nearly a quarter of MMC enrollees lived during the study period.…”
Section: Introductionmentioning
confidence: 99%